The Employability Skills Performance of Business Graduates in Malaysia: Do Employers, Graduates and Academicians Speak the Same Language? - Erni, Tanius; Husna, Binti Johari; Astri`, Yulia; Heng, Chin Siong; Khairul Hanim, Pazim (AESS Publications, 2018)
Employability skills may implicate and reflect the employment opportunity especially among the new graduates. This study aims to compare the performance of employability skills among new business graduates in Malaysia base on stakeholder perceptions; they are the employer, academician and new graduate. Besides, is to identify if there is any significant difference between their opinions. Three sets of questionnaires were established to evaluate employability skills; they are basic, applied, interpersonal and 21st-century skills. The result revealed that stakeholders rated the performance of new graduate high and interpersonal skill is the most performed. The result also revealed that they speak in a different language in which specific skills is the most important than the others. Accordingly, recommendations and limitations highlighted in this study